Corporate foundations and public policy advocacy through stakeholder network management: the NiñezYA case in Colombia (2020)
This article explores the possibilities of network management to increase the capacity of business foundations to exert influence on the process of agenda-setting in public policies. This case illustrates how three foundations (Éxito Foundation, Alpina Foundation and ALAS Foundation) helped to coordinate one hundred civil society organizations to influence the Colombian National Development Plan (2018-2022). The case shows that business foundations can play an important role in setting the policy agenda by working as articulators of multiple fragmented actors of civil society. The article details the specific mechanisms used to pursue this articulation through the creation of a policy network known as NiñezYA. This in turn suggests that other foundations and NGOs could use the same strategies to increase their influence in policy making.